Лучше быть святым: романы / Чингиз Абдуллаев - Абдуллаев Чингиз Акифович (Схватка без правил, 1995)
Экземпляры: ФО-32 (20110615) / Инвентарный номер: 46982 / Цена: 20.00 / Сис.шифр: Р2 / Авт.знак: А 13 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6